Artificial intelligence in innovation processes. A study using the example of an innvation research institute - Malte Busch; Daniel Duwe (Fraunhofer-Institut für System- und Innovationsforschung, 2023)
Artificial Intelligence (AI) is playing an increasingly important role in innovation processes. Using the example of an innovation research institute, this paper examines the role that AI plays in the institute's innovation processes, how experts from the various departments assess the impact of AI and what challenges they see. The paper brings together findings from systematically analysed AI and innovation literature with the qualitative assessments of employees. – – Künstliche Intelligenz (KI) spielt eine immer wichtigere Rolle in Innovationsprozessen. Am Beispiel eines Innovationsforschungsinstitut untersucht dieses Papier, welche Rolle KI in den Innovationsprozessen des Instituts spielt, wie die Experten aus den unterschiedlichen Abteilungen die Auswirkungen von KI einschätzen und welche Herausforderungen sie sehen. Das Papier bringt Erkenntnisse aus systematisch analysierter KI- und Innovationsliteratur mit den qualitativen Einschätzungen der Mitarbeiter zusammen.
Keywords: 330; Innovation process; Artificial intelligence (AI); Research Institute; Innovationsprozess; Künstliche Intelligenz (KI); Forschungsinsitut